Characterization and phylogenetic analysis of the complete mitochondrial genome of Mango tilapia (Sarotherodon galilaeus: Cichlidae) - Yosur G. Fiteha; M. A. Rashed; R. A. M. Ali; M. Magdy (Molecular Biology Reports, 2023)
Background Sarotherodon galilaeus (Linné, 1758) is a member of the family Cichlidae, which is considered the most important aquaculture freshwater species endemic to Africa and the Middle East. The genetics and molecular biology of this species are rare. This requires more comprehensive mitochondrial genomes-based phylogenetics to enhance understanding of the relationship and delineate this species. Methods and results Here, we assembled the complete mitogenome of S. galilaeus using Illumina high-throughput sequencing technology. The mango tilapia mitogenome was 16,631 bp in length with an AT composition of 53.4% and 46.4% GC content. It encodes 37 genes comprising two ribosomal RNA genes (rRNAs), 22 transfer RNA genes (tRNAs), and 13 protein-coding genes (PCGs) as well as the D-loop known as the control region. The phylogenetic tree was conducted to provide a relationship within the haplotilapiine lineage based on the maximum likelihood method, and the newly sequenced S. galilaeus was clustered with other Sarotherodon species. Conclusion Our results provide a new perception of the genetic basis of S . galilaeus species for further research on systematics, evolution, population genetics, and molecular ecology.